EUS-guided fine needle biopsy is able to provide diagnosis in rare osteoclast-like giant cells undifferentiated carcinoma of the pancreas: report of two cases - Pop Ruxandra Mihaela; Diaconu Claudia Irina; Rimbaş Mihai; Mateescu Radu Bogdan; Rouhani Farid; Popp Cristiana; Manfrin Erminia; Crinò Stefano Francesco; Cauni Victor (Sciendo, 2023)
Undifferentiated carcinoma of the pancreas with osteoclast-like giant cells (UC-OGC) is a rare subtype of pancreatic cancer, accounting for less than 1% of all pancreatic tumors. Preoperative diagnosis is cumbersome as cross-sectional imaging is often not capable to distinguish between UC-OGC and other pancreatic tumors such as pancreatic adenocarcinoma, mucinous carcinoma or neuroendocrine tumors and specific tumor markers seem to be lacking. Endoscopic ultrasound r `m(EUS) with tissue acquisition via fine-needle aspiration (FNA) or biopsy (FNB) with microscopic HE staining and immunohistochemistry allows for an accurate diagnosis, thus influencing further treatment. We present herein the cases of two patients with osteoclast-like giant cells tumors of the pancreas diagnosed by EUS-guided fine needle biopsy and perform a literature review on the role of EUS-guided biopsy for diagnosis.